Acute Psychosocial Stress-Mediated Changes in the Expression and Methylation of Perforin in Chronic Fatigue Syndrome. (January 2013) - Falkenberg, Virginia R.; Whistler, Toni; Murray, Janna R.; Unger, Elizabeth R.; Rajeevan, Mangalathu S.
Perforin ( PRF1 ) is essential for immune surveillance and studies report decreased perforin in chronic fatigue syndrome (CFS), an illness potentially associated with stress and/or infection. We hypothesize that stress can influence regulation of PRF1 expression, and that this regulation will differ between CFS and non-fatigued (NF) controls. We used the Trier Social Stress Test (TSST) as a standardized acute psychosocial stress, and evaluated its effect on PRF1 expression and methylation in CFS (n = 34) compared with NF (n = 47) participants. During the TSST, natural killer (NK) cells increased significantly in both CFS ( P = <0.0001) and NF subjects ( P = <0.0001). Unlike previous reports, there was no significant difference in PRF1 expression at baseline or during TSST between CFS and NF. However, whole blood PRF1 expression increased 1.6 fold during the TSST in both CFS ( P = 0.0003) and NF ( P = <0.0001). Further, the peak response immediately following the TSST was lower in CFS compared with NF ( P = 0.04). In addition, at 1.5 hours post TSST, PRF1 expression was elevated in CFS compared with NF (whole blood, P = 0.06; PBMC, P = 0.02). Methylation of seven CpG sites in the methylation sensitive region of the PRF1 promoter ranged from 38%-79% with no significant differences between CFS and NF. Although, the average baseline methylation of all seven CpG sites did not differ between CFS and NF groups, it showed a significant negative correlation with PRF1 expression at all TSST time points in both CFS (r = –0.56, P = <0.0001) and NF (r = –0.38, P = <0.0001). Among participants with high average methylation (≥65%), PRF1 expression was significantly lower in CFS than NF subjects immediately following TSST. These findings suggest methylation could be an important epigenetic determinant of inter-individual differences in PRF1 expression and that the differences in PRF1 expression and methylation between CFS and NF in the acute stress response require further investigation.